Predicting self-harm in prisoners: risk factors and a prognostic model in a cohort of 542 prison entrants - Ryland, H; Gould, C; McGeorge, T; Hawton, K; Fazel, S (Elsevier, 2020)
Background: Self-harm is common in prisoners. There is an association between self-harm in prisoners and subsequent suicide, both within prison and on release. The aim of this study is to develop and evaluate a prediction model to identify male prisoners at high risk of self-harm.